Best Answer

-5u + 4 + 8u = 43

simplify by subtracting 4 from both sides of the equation to get rid of the 4 on the left:

-5u + 8u = 43

Simplify further by combining the -5u and the 8u:

3u = 43

Divide both sides by 3 to solve for u:

u = 43/3

rewrite the fraction:

u = 14 1/3

Q: -5u plus 4 plus 8u equals 43?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

Related questions

13u

u = 7

If: 8u = -96 Then: u = -12

For a suitable value of u, it can be.

7u.

uhm...if u are talking about math then the answer is... -8u

Is 24u^2 + 35

It is a linear equation in the variable u.

24u to the second power. Differentiate 40u to the fifth power which is 200u to the fourth power and 5u to the second power which is 10u. Subtract 400u to the sixth power from 1000u to the sixth power which is 600u to the sixth power. Then square 5u to the second power which is 25u to the fourth power. Finally, divide 600u to the sixth power by 25u to the fourth power. The solution is 24u to the second power. Another method is simplifying it to 8u cubed (to the third power) and taking the power rule. Take 3 times 8u which is 24u and subtract 1 from 3 in exponent which is 2. The answer is 24u to the second power.

(8u)^5 = (8)^5 x (u)^5 = 32768xu^5

17

add 8 and 2 then take away 3. even u should get 7u.